Second trimester abnormal uterine artery Dopplers and adverse obstetric and neonatal outcomes when PAPP-a is normal - Jie, Michelle; Jaufuraully, Shireen; Lambert, James; Napolitano, Raffaele; Siassakos, Dimitrios (The journal of maternal-fetal & neonatal medicine, 2023)
What are the novel findings of this work? Pregnancies with abnormal uterine artery Dopplers at the time of the anomaly scan and normal PAPP-A are at increased risk of having pre-eclampsia, small for gestational age fetuses, emergency cesarean, neonatal unit admission (including but not limited to prematurity), and neonatal hypoglycemia. What are the clinical implications of this work? Due to the significantly increased risk of adverse maternal and neonatal outcomes in first time mothers with increased uterine artery Dopplers despite normal PAPP-A, ultrasound assessment of placental function should be offered to all during their anomaly scans, subject to resources, to aid antenatal management and counseling. Further research is needed into undiagnosed diabetes. To explore the association between abnormal uterine artery Dopplers (combined PI > 2.5) - with normal PAPP-A - and adverse obstetric/neonatal outcomes. This was a retrospective cohort study of 800 patients between 1 March 2019 − 23 November 2021 in a tertiary UK hospital, where it is routine to measure uterine artery Dopplers of all pregnancies during their anomaly scans. 400 nulliparous women/birthing people with complete data were included. 400 nulliparous controls scanned in the same time frame (1.5 years) with normal PAPP-A and uterine artery Dopplers were matched for age and BMI. Outcomes included: mode of birth, postpartum complications, birth weight/centile, Apgar score, gestational age at delivery, neonatal unit admission, and clinical neonatal hypoglycemia. Multivariable analysis was used. Compared to controls, pregnancies with abnormal uterine artery Dopplers and normal PAPP-A were at increased risk of induction (46.5% vs 35.5%, p = .042), cesarean section (46.0% vs 38.0%, p = .002), emergency cesarean section (35.0% vs 26.5%, p = .009), and pre-eclampsia 5.8% vs 2.5%, p = .021). Their babies were more likely to be admitted to the neonatal unit - mostly for prematurity (15.3% vs 6.3%, p = .0004), hypoglycemia (4.0% vs 1.0%, p = .007), be small for gestational age (26.5% vs 11.5%, p = .0001), had intrauterine growth restriction (10.8% vs 1.3%, p = .0001), and be born prematurely (10.0% vs 3.5%, p = .002). Routine measurement of uterine artery Dopplers increased the detection rate of small for gestational age fetuses by 15.1%. Over half of the babies admitted with neonatal hypoglycemia in pregnancies with abnormal uterine artery Dopplers had an unexplained cause. Pregnancies with abnormal uterine Dopplers are not only at increased risk of pre-eclampsia and small for gestational age fetuses/intrauterine growth restriction, but are also at increased risk of emergency cesarean section and adverse neonatal outcomes. The increased incidence of neonatal hypoglycemia is likely driven to some degree by prematurity and placental complications, but possibly also by undiagnosed glucose dysmetabolism. This may warrant routine measurement of uterine artery Dopplers in all pregnancies (regardless of risk), where feasible, to aid antenatal management and counseling.